Asymmetric Catalytic (2+1) Cycloaddition of Thioketones to Synthesize Tetrasubstituted Thiiranes. (9th March 2022) - Lin, Xiaobin; Pu, Maoping; Sang, Xinpeng; Li, Shiyang; Liu, Xiaohua; Wu, Yun‐Dong; Feng, Xiaoming
Abstract: Herein, we report the first example of enantioselective (2+1) cycloaddition of thioketones with α‐diazo pyrazoleamides for the direct synthesis of tetrasubstituted thiiranes. In the presence of chiral N, N′ ‐dioxide/cobalt(ΙΙ) complexes (2–5 mol%), excellent efficiency (up to 99 % yield within 15 mins) and high stereoselectivity (up to >19 : 1 dr and 97 % ee) are available. Elaborations of thiiranes via desulfuration have also been conducted to deliver tetrasubstituted olefins. Density functional theory calculations reveal that the reaction initiates from a doublet state cobalt(ΙΙ) carbenoid, which is followed by a quartet cobalt(ΙΙ)‐bound thiocarbonyl ylide pathway. This work provides a route for the selective construction of tetrasubstituted thiiranes and olefins that are otherwise difficult to access. Abstract : The first example of catalytic enantioselective (2+1) cycloaddition of α‐diazo pyrazoleamides with thioketones is presented, catalyzed by chiral N, N′ ‐dioxide/Co ΙΙ complexes. This method provides a rapid and facile access to a series of optically active tetrasubstituted thiiranes with good outcomes (up to 99 % yield, 97 % ee). The origin of stereoselectivity was well elucidated by DFT calculations.